Análise da aplicação do Procel Reluz no sistema de iluminação pública da Escadaria de Santo Antônio no município de Tucuruí-PA - SANTOS, Luiz Augusto da Silva (2019)
The Energy Research Company (ERC), in a survey released in mid-2016, disclosed that public lighting in 2015 was responsible for the consumption of 74,103,053 MWh in Brazil. To reduce these costs, Eletrobrás created the ReLuz program to increase energy efficiency in public lighting by replacing obsolete materials, commonly used in street lighting, for more efficient ones with the goal of reducing the energy consumption and improve night lighting. In this work we will from the contextualization of ReLuz, the energy supply conditions to public lighting in Tucuruí, to the analyzes of different new equipment available to public lighting. In addition, we present a study of the economic alternatives to create the program in Tucuruí’s using calculation methods based on ReLuz instruction manual to emphasize the technical and economic aspects of the project. Moreover, this paper presents the requirements for the development of an efficient public lighting project, based on PROCEL manuals. The main concepts of public lighting are addressed; a comparison is made of different technologies used in street lighting, highlighting those of greater energy efficiency. In the last part, we show of simulation of an efficient project for public lighting in Tucuruí – PA.